Larrikins? Wowsers? Hipsters? Snags? What does it mean to be a 'real man' in modern-day Australia?. (September 2019) - Adegbosin, Adeyinka Emmanuel; Plummer, David; Yau, Matthew; Franklin, Richard; Cordier, Reinie; Sun, Jing
Gender is constructed from social and cultural meanings that dynamically shift and vary. Previous work has assumed that the constructions of masculinity in Australia are like those in other Western societies, and typically focus on qualities such as physical strength, courage and sometimes military engagement. This study explores whether these assumptions hold, by conducting telephone interviews among 617 Queensland men, aged 18 years and above, across all geographical parts of Queensland. This survey was administered in 2013, as part of the Queensland Social Survey series. The study explores the diverse meanings associated with being a 'real man' given by the survey participants. Three main dimensions emerged from the thematic analysis: physicality; personality and character; social roles and relationships. The study confirmed that masculinities are dynamic and complex. Responses revealed a surprising emphasis on character and morality 44.5% (n = 684) as defining manhood, as against physical qualities 13.7% (n = 153).